The impacts of port disruptions on supply chain - Su, Shiling. (2011)
Nowadays, competition is between one supply chain and another supply chain instead of among companies. However, ports are often neglected despite its importance in a supply chain. Therefore, the aim of the paper is to study the impacts of port disruptions in East Asia from 2001 to 2011. East Asia in this case includes China, Hong Kong, Macau, Taiwan, North Korea, South Korea, Japan, The Philippines, Vietnam, Singapore, Malaysia, Thailand, Brunei Darussalam, Myanmar, Cambodia, Timor-Leste, Indonesia, India and Bangladesh. This is carried out by secondary research whereby disruptions were identified and both severity and likelihood were quantified. Further insights were gained by interviews with terminal operators and shipping lines. Mitigation strategies were also given.